2016
DOI: 10.1016/j.jcmg.2015.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Coronary Calcium on Standard Chest CT Scans With Mortality

Abstract: STRUCTURED ABSTRACT Objectives We aimed to determine the correlation between coronary artery calcium (CAC) scores on 3mm ECG-gated computed tomography (CT) scans and standard 6mm chest CT scans, and to compare relative strength of associations of CAC on each scan type with mortality risk. Background Coronary artery calcification predicts cardiovascular disease (CVD) and all-cause mortality, and is typically measured on ECG-gated 3mm CT scans. Patients undergo standard 6mm chest CTs for various clinical indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 22 publications
1
62
0
1
Order By: Relevance
“…In the gated 3mm versus nongated 6mm study discussed above, 64 each SD higher CAC yielded identically increased OR for all cause mortality of 1.5. Compared to 0 CAC, the OR for the 1e100, 101e300 and > 300 categories were 1.9, 2.3 and 2.6 respectively for the 6mm nongated scans, and 2.1, 2.9 and 3.2 for the 3mm gated scans respectively, in models fully adjusted for risk factors.…”
Section: Prognostic Valuementioning
confidence: 88%
See 1 more Smart Citation
“…In the gated 3mm versus nongated 6mm study discussed above, 64 each SD higher CAC yielded identically increased OR for all cause mortality of 1.5. Compared to 0 CAC, the OR for the 1e100, 101e300 and > 300 categories were 1.9, 2.3 and 2.6 respectively for the 6mm nongated scans, and 2.1, 2.9 and 3.2 for the 3mm gated scans respectively, in models fully adjusted for risk factors.…”
Section: Prognostic Valuementioning
confidence: 88%
“…63 Most recently, 4544 subjects underwent both 3mm gated CAC scans and 6 mm standard nongated chest CT scans by electron beam computed tomography, with a 6 year follow up for all cause mortality. 64 There were 157 deaths, matched 1:3 to 494 survivor controls. There was excellent correlation between the 2 scans in the 651 subjects (r ¼ 0.93, p < 0.001); the median CAC scores were lower on the 6 mm scan (22 versus 104 Agatston units, p < 0.001), consistent with the decreased sensitivity of thicker slices to detect CAC.…”
Section: Nongated Ct Examinationsmentioning
confidence: 99%
“…Prior results have shown good correlation of the calcium score on non-gated CT compared to dedicated ECG gated calcium CT scoring 2, 20 . Although a high calcium score is predictive of coronary artery disease, the calcium score is understood as a marker of disease, rather than direct visualization of coronary stenosis.…”
Section: Discussionmentioning
confidence: 95%
“…However, even using older generation CT scans, coronary artery calcification scores can be obtained from routine non-contrast chest CT (i.e., CT performed for non-cardiac indications) 2 . These calcium score findings may be “incidental” to the primary indication for the chest CT, but may be important to patient care 3 .…”
Section: Introductionmentioning
confidence: 99%
“…One prior lung cancer screening study showed that visual estimation of coronary calcification found on non‐gated chest CT are comparably predictive of cardiovascular events compared to Agatston scoring . The incidental identification of coronary calcification itself can be predictive of future cardiovascular events, and these results emphasize the importance of identifying these higher‐risk patients to provide preventive care …”
Section: Introductionmentioning
confidence: 98%